Keamanan Situs Web Crowdfunding melalui Implementasi Teknologi Blockchain Polygon - Rafi Johari; Viddi Mardiansyah (Jurnal Sistem Informasi, 2025)
This study aims to enhance the security and transparency of crowdfunding platforms by implementing Polygon blockchain technology. Traditional crowdfunding systems are often vulnerable to fund mismanagement and lack accountability. To address these issues, a blockchain-based crowdfunding website was developed using smart contracts deployed on the Polygon network. The project follows a software engineering approach using the prototyping development model. The system is built using Solidity for smart contracts and React.js for the frontend, integrated with the MetaMask crypto wallet for authentication and transaction execution. The implementation results show that the system successfully facilitates secure, transparent, and decentralized donation processes. All transactions and fund flows are permanently recorded and verifiable through PolygonScan. User validation is conducted without conventional login systems, relying instead on wallet-based authentication, which reduces the risk of credential theft. Functional testing confirms that all core features perform as expected, including donation program selection, transaction history recording, and MetaMask integration. In conclusion, the developed system successfully achieves the research objective of providing a more secure and trustworthy crowdfunding platform through the application of Polygon blockchain technology.   Keywords:  Blockchain, crowdfunding, Polygon, smart contract, MetaMask, data security.